1963
DOI: 10.1002/j.2050-0416.1963.tb01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Phenotypic Variations in the Flocculence Character of Yeast

Abstract: The protein and polysaccharide composition of the yeast cell wall has been examined, with the aim of explaining phenotypic variations in the flocculence character which occur during fermentation. The results show that the period of deflocculation coincides with a synthesis of mannan. Accordingly, this polysaccharide appears to act as a regulator of the intensity of flocculation by masking more or less completely the active groups of the specific fraction carrying the flocculence character. Comparative study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…According to Masschelein et al (1963), the mannoproteins of yeast walls play a fundamental role in flocculation, the walls of flocculent strains having more mannans than those of nonflocculent strains. However, this view was criticized by Griffin & MacWilliam (1969), who failed to demonstrate any differences in the amounts of these polymers between flocculent and non-flocculent yeasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Masschelein et al (1963), the mannoproteins of yeast walls play a fundamental role in flocculation, the walls of flocculent strains having more mannans than those of nonflocculent strains. However, this view was criticized by Griffin & MacWilliam (1969), who failed to demonstrate any differences in the amounts of these polymers between flocculent and non-flocculent yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that flocculation of these two strains was controlled by the Ca2+/K+ ratio in the medium. The chemical composition of the yeast cell wall changes during the development of the yeast (Bonaly et al, 1971) and flocculation phenomena depend directly on the components of the wall (Masschelein et al, 1963). The nature of these cell wall components and the effect that they have are the subject of contrasting theories concerning the phenomenon of yeast flocculation (Lyons & Hough, 1970, 1971Griffin & MacWilliam, 1969;Mill, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…But it is at present unknown whether flocculation onset is There are several pieces of evidence tending to suggest involvement of mannan receptors in flocculation onset. Cell-wall mannan content was originally implicated in flocculation some 30 years ago (Devreux, 1962;Masschelein et al, 1963;Windisch, 1968). Flocculent cell-walls of S. cerevisiae have been shown to contain more mannan (Stewart and Garrison, 1972;Stewart, 1975), as has also been reported in Kluyveromyces bulgaricus (Al-Mahmood et al, 1987) and Pichia pastoris (Mbawala et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The content of acid-soluble glycogen is correlated with the process of yeast flocculation [15]. Glycogen content is found to be higher in flocculant yeast strains than in powdery varieties [16]. In yeast, presence of glycogen in the form of a-glucans at cell-surface level of yeast and its role in flocculation are confirmed by using amyloglucosidase treatment.…”
Section: Introductionmentioning
confidence: 89%